Automatic evaluation of migration quality in distributed networks of converters - Ferreira, Miguel (2005)
Migration has always played an important role in digital preservation. The most recent developments in this context introduce networks of remotely distributed converters. In this paper we propose an extension to current migration networks to enable users to: a) determine to what extent have the essential characteristics of digital objects been preserved during a migration; b) generate detailed migration reports for inclusion in the objects’ preservation metadata; and c) provide advice on the available migration paths or target formats that will best suit users’ requirements.